Association between 24-hour movement guidelines and working memory in early Chinese adolescents - Xue, Peng; Han, Tong; Jin, Xinlan; Li, Wen; Chen, Yiyi (Frontiers in Psychology, 2025)
ObjectiveThis study aimed to examine the association between adherence to the 24-hour movement behavior guidelines and WM performance in early adolescents, particularly the cumulative and gender-specific effects.MethodsA cross-sectional study was conducted on 2,163 adolescents aged 11–14 years. Participants’ adherence to the 24-hour movement guidelines was assessed using validated questionnaires. WM performance was measured via a computerized N-back task, including 1-back and 2-back conditions, with reaction time recorded as the primary outcome indicator. Statistical analyses (including descriptive statistics and regression analysis) were performed to explore the relationship between guideline adherence and WM performance, and gender-stratified analysis was further conducted.ResultsOnly 2.9% of participants met none of the 24-hour movement guidelines, while 27.2% met all three guide-lines; significant gender differences in adherence were observed (p < 0.05). A significant negative dose-response relationship was found between the number of guidelines met and reaction times in the N-back tasks (p < 0.01). The above dose-response effect was only significant in girls (2-back task: F = 15.095, p < 0.001), with no significant differences detected in boys. The dose-response trend was more pronounced under higher cognitive load conditions (2-back task, p < 0.01). Adolescents who met both screen time and sleep recommendations exhibited the best WM performance (shortest reaction time, p < 0.05).ConclusionThis study identifies a notable, dose-dependent association between adherence to multiple components of 24-hour movement behavior guidelines and better WM performance in early adolescence, with this pattern being particularly evident under high cognitive load conditions and girls showing greater sensitivity. The findings indicate that adherence to the 24-hour movement guidelines, particularly the combined reduction of screen time and adequate sleep duration, is associated with better WM performance during early adolescence.